CLOCK-BMAL1 regulates circadian oscillation of ventricular arrhythmias in failing hearts through β1 adrenergic receptor - Zhou, Zihao (Am J Transl Res, 2020)
The incidence of ventricular arrhythmias (VAs) in chronic heart failure (CHF) exhibits a notable circadian rhythm, for which the underlying mechanism has not yet been well defined. Thus, we aimed to investigate the role of cardiac core circadian genes on circadian VAs in CHF. First, a guinea pig CHF model was created by transaortic constriction. Circadian oscillation of core clock genes was evaluated by RT-PCR and was found to be unaltered in CHF (P > 0.05). Using programmed electrical stimulation in Langendorff-perfused failing hearts, we discovered that the CHF group exhibited increased VAs with greater incidence at CT3 compared to CT15 upon isoproterenol (ISO) stimulation. Circadian VAs was blunted by a β1-AR-selective blocker rather than a β2-AR-selective blocker. Circadian oscillation of β1-AR was retained in CHF (P > 0.05) and a 4-h phase delay between β1-AR and CLOCK-BMAL1 was recorded. Therefore, when CLOCK-BMAL1 was overexpressed using adenovirus infection, an induced overexpression of β1-AR also ensued, which resulted in prolonged action potential duration (APD) and enhanced arrhythmic response to ISO stimulation in cardiomyocytes (P < 0.05). Finally, chromatin immunoprecipitation and luciferase assays confirmed that CLOCK-BMAL1 binds to the enhancer of β1-AR gene and upregulates β1-AR expression. Therefore, in this study, we discovered that CLOCK-BMAL1 regulates the expression of β1-AR on a transcriptional level and subsequently modulates circadian VAs in CHF.